PENINGKATAN HASIL BELAJAR PENDIDIKAN PANCASILA SISWA KELAS IV DENGAN MODEL NUMBERED HEADS TOGETHER DI SD NEGERI 1 TARATAK BARU SIJUNJUNG - Yulfia Nora; Refnywidialistuti; Dea Febriola Inesti (Ekasakti Jurnal Penelitian dan Pengabdian, 2024)
The purpose of the research is to describe the improvement of student learning outcomes in Pancasila Education by using the Numbered Heads Together model.. The type of research used is PTK (Classroom Action Research) with steps including planning, implementation, observation and reflection. steps include planning, implementation, observation and reflection. This research was carried out in two cycles, each cycle consisted of two meetings and ended with a test. Subjects in this study were fourth grade students of SD Negeri 1 Taratak Baru, Sijunjung. The research instruments used include observation sheets teacher activity observation sheet, student affective assessment sheet, test sheet. Based on the results data analysis obtained the percentage of completeness of student learning outcomes in cycle I was 31.81% with an average of 72.95, increasing in cycle II by 90.90% with an average of 84.54. with an average of 84.54. Meanwhile, the completeness of students' affective learning outcomes in the cycle I, obtained by 49.49% with an average of 73.48, increased in cycle II by 84.08% with an average of 84.54. cycle II amounted to 84.08% with an average of 93.93. From the research results it can be It can be concluded that the Numbered Heads Together model can improve the cognitive and affective aspects of learning outcomes of grade IV students at SD Negeri 1 Taratak Baru Sijunjung.